Prevalence and impact of oral pain in 8-year-old children in Sri Lanka - N. RATNAYAKE, & L. EKANAYAKE (Paediatric Dentistry, 2005)
The present study aimed to determine the prevalence and impact of oral pain in 8-year-old Sri Lankan children and their parents.